The PERCIVAL detector: first user experiments. (25th November 2022) - Correa, J.; Mehrjoo, M.; Battistelli, R.; Lehmkühler, F.; Marras, A.; Wunderer, C. B.; Hirono, T.; Felk, V.; Krivan, F.; Lange, S.; Shevyakov, I.; Vardanyan, V.; et al.
Abstract : PERCIVAL is a detector system specifically designed for the soft X‐ray regime. Although still in a development phase, it has already served its first user experiments at both a storage ring and also a free‐electron laser. The device performed remarkably well in all the different techniques tested: ptychography, holography and also X‐ray photon correlation spectroscopy. The results of these tests are presented. Abstract : The PERCIVAL detector is a CMOS imager designed for the soft X‐ray regime at photon sources. Although still in its final development phase, it has recently seen its first user experiments: ptychography at a free‐electron laser, holographic imaging at a storage ring and preliminary tests on X‐ray photon correlation spectroscopy. The detector performed remarkably well in terms of spatial resolution achievable in the sample plane, owing to its small pixel size, large active area and very large dynamic range; but also in terms of its frame rate, which is significantly faster than traditional CCDs. In particular, it is the combination of these features which makes PERCIVAL an attractive option for soft X‐ray science.